2020
DOI: 10.1038/s41467-019-14112-2
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of TCR-induced transcription by Bach2 controls regulatory T cell differentiation and homeostasis

Abstract: Differentiation and homeostasis of Foxp3 + regulatory T (Treg) cells are strictly controlled by T-cell receptor (TCR) signals; however, molecular mechanisms that govern these processes are incompletely understood. Here we show that Bach2 is an important regulator of Treg cell differentiation and homeostasis downstream of TCR signaling. Bach2 prevents premature differentiation of fully suppressive effector Treg (eTreg) cells, limits IL-10 production and is required for the development of peripherally induced Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 68 publications
8
68
0
Order By: Relevance
“…The perturbations in signalling molecules we see following activation of T cells from older donors and their increased expression of IRF4 led us to hypothesise that IRF4 may regulate RBPJ expression. Reanalysis of recently published RNA‐Seq data showed that Irf4 ‐deficient mouse CD4 + T cells had reduced levels of Rbpj gene expression following activation (Log2 FC = −0.89, p = 8.62 × 10 −5 ; (Sidwell et al, 2020). We re‐analysed the published ATAC‐Seq and ChIP‐Seq libraries from this work to look at the potential IRF4‐dependent regulation of Rbpj expression.…”
Section: Resultsmentioning
confidence: 99%
“…The perturbations in signalling molecules we see following activation of T cells from older donors and their increased expression of IRF4 led us to hypothesise that IRF4 may regulate RBPJ expression. Reanalysis of recently published RNA‐Seq data showed that Irf4 ‐deficient mouse CD4 + T cells had reduced levels of Rbpj gene expression following activation (Log2 FC = −0.89, p = 8.62 × 10 −5 ; (Sidwell et al, 2020). We re‐analysed the published ATAC‐Seq and ChIP‐Seq libraries from this work to look at the potential IRF4‐dependent regulation of Rbpj expression.…”
Section: Resultsmentioning
confidence: 99%
“…Repression of IFN-γ expression is a critical biological function of BACH2 not only in conventional CD4 + Th1 cells and CD8 + T cells, but also during early iT reg cell development, where BACH2-mediated repression of IFN-γ is required for stabilization of iT reg differentiation prior to Foxp3 induction 11 13 . Moreover, we and others have shown that within lineage-committed Foxp3 + T reg cells, BACH2 is re-purposed and is not required to maintain Foxp3 expression or suppress IFN-γ expression, but rather blocks the TCR-driven transition between resting T reg (rT reg ) and activated T reg (aT reg ) states 20 , 21 . Given these observations, we chose to study the regulation of Ifng expression by BACH2 in the Foxp3-negative Jurkat cell line.…”
Section: Discussionmentioning
confidence: 97%
“…5b,c). The CD4_Tfr cluster correlated with cognate stimulated CD4_Stim4.3 cluster with genes (IL18R1, FOXP1, BCL2, TRAF4) related to the activation and maintenance of Tregs [62][63][64][65] (Fig. 5d,l).…”
Section: Cd38 + Ptreg-infiltrates Correlate With Poor Clinical Outcommentioning
confidence: 92%